The Impact of Direct Expenditures of Diving Tourism Towards The Economy of Coastal Balinese - I Wayan Suardana; Saroyeni Piartini; Ni Made Ariani (Research and Community Services Institutes of Udayana University, 2017)
This research illustrates the extent of correlation between the local economy and marine ecosystem services. Apart from being recreational destinations oriented to the economy, Tulamben and Pemuteran are places where coral reefs ecosystem grows and develops. Hence, it needs to be properly conserved. This study found the estimated number of tourists who dive and snorkel in these two areas, it reaches 297.752 per year, with actual annual expenditures amount to US 283.2 million. The economic impact of the whole diving tourism in Tulamben and Pemuteran approximately ranges from US 396.4 million to US 1.059.7 million per year. The high economic value achieved by the government and the local communities as a whole indicates a significant increase of diving activities in both areas. This result suggests that local economy and marine ecosystem services are closely related. However, tourism and the perception aroused about the environmental issues and values not only provide opportunities for macro business improvement but also pose a threat to the sustainability of the underwater ecosystem.